2006
DOI: 10.1103/physrevlett.96.083602
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Power Lasers for Detection of Elastic Photon-Photon Scattering

Abstract: The properties of four-wave interaction via the nonlinear quantum vacuum is investigated. The effect of the quantum vacuum is to generate photons with new frequencies and wave vectors, due to elastic photon-photon scattering. An expression for the number of generated photons is derived and using state-of-the-art laser data it is found that the number of photons can reach detectable levels. In particular, the prospect of using the high repetition Astra Gemini system at the Rutherford Appleton Laboratory is disc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(148 citation statements)
references
References 20 publications
6
142
0
Order By: Relevance
“…In this laser-assisted setup the "signal" of photon-photon scattering is, of course, the remaining outgoing photon. In Lundin et al, 2007 andLundström et al, 2006 an experiment has been suggested to observe laser-assisted photon-photon scattering with the Astra-Gemini laser system (see Sec. II.A).…”
Section: Experimental Suggestions For Direct Detection Of Photon-photmentioning
confidence: 99%
“…In this laser-assisted setup the "signal" of photon-photon scattering is, of course, the remaining outgoing photon. In Lundin et al, 2007 andLundström et al, 2006 an experiment has been suggested to observe laser-assisted photon-photon scattering with the Astra-Gemini laser system (see Sec. II.A).…”
Section: Experimental Suggestions For Direct Detection Of Photon-photmentioning
confidence: 99%
“…Recently, indications have been reported for the relevance of QED vacuum birefringence for optical polarimetry of a neutron star [36]. Other theoretical proposals for optical signatures of quantum vacuum nonlinearity have focused on photon-photon scattering in the form of laser-pulse collisions [37][38][39][40], interference effects [41][42][43][44], quantum reflection [45,46], photon merging [47][48][49][50][51], photon splitting [19,[52][53][54][55][56][57][58][59][60], and higher-harmonic generation from laser driven vacuum [61][62][63][64]. Finally, and perhaps most strikingly, strong electric fields can facilitate the spontaneous formation of real electron-position pairs from the QED vacuum via the Schwinger effect [2,14,15].…”
Section: Jhep03(2017)108mentioning
confidence: 99%
“…Similar to the classic four-wave mixing process, the quantum vacuum effect can generate photons with new frequencies by four-wave interaction due to elastic photonphoton scattering [2]. Recently the matterless double slit was suggested to observe the photon-photon scattering and to realize the controlling of light with light [3,4].…”
Section: Introductionmentioning
confidence: 99%